Synthesis, characterization and applications of pH controlled Fe2O3 nanoparticles for electrocatalytic hydrogen evolution reaction. (23rd November 2018) - Ali, Rai Nauman; Naz, Hina; Zhu, Xingqun; Xiang, Junxiang; Hu, Guojing; Xiang, Bin
Abstract: Non-noble and earth abundant catalysts provide an alternative route for efficient hydrogen evolution reaction of clean and renewable energy systems. Here, we report the synthesis of Fe2 O3 nanoparticles by hydrothermal method by adjusting the pH value at 12 and 14 during the reaction. The as-synthesized samples are then subjected to structure and morphology characterization by x-ray diffraction and transmission electron microscopy. The chemical components of the as synthesized samples are characterized by x-ray photoelectron spectroscopy. Finally, the electrochemical measurements have been done to evaluate the catalytic performance of Fe2 O3 nanoparticles. A high HER performance at pH 12 and pH 14 is well noticed for Fe2 O3 nanoparticles by linear sweep voltammetry experiment, including a low overpotential of 321 mV and 423 mV at 10 mAcm −2 and Tafel slope values of 140 mv/dec and 144 mV/dec in basic medium, respectively. Moreover, the polarization curves after 1000 CV cycles has also shown the excellent stability of Fe2 O3 nanoparticles for HER. Our work provides a new path for the design and synthesis of novel nanostructure electrocatalysts.